(untitled) (Journal of Engineering Studies and Research, 2022)
Waste Steel Fibre (WSF) and Rice Husk Ash (RHA) were used in the production of Self Compacting Concrete (SCC). Seven variants of SCC mixes were prepared. The rheological and mechanical properties (Compressive Strength (CS) and Split Tensile Strength (STS)) of the SCC produced were examined. The results showed that the blocking ratio varied marginally while other fresh properties of the SCC with WSF compared favourably to the standard. The CS of the hardened control samples after 56 days of curing was 36.18 N/mm2 while the CS of SCC with 15 % of RHA and 0.0 %-0.5 % of WSF, ranged from 37.04 - 43.64 N/mm2 with the maximum CS at 0.4 % WSF addition. Similarly, the STS of SCC at 56 days improved with an increase in WSF content up to 0.4 % and decreased with further addition of WSF. The inclusion of WSF at the optimum level of 0.4 % addition had a better influence on the tensile strength of SCC thereby increasing the ratio of STS to CS.